Petrographic and Economic Aspects of the Sandstone Unit of the Kamlial Formation, Karaat Hills, South-Eastern Kohat Plateau, NW Pakistan - Khan, M. A.; Khattak, N. U.; Ali, B.; Yar, M.; Mahmood, M. F.; Abuzar, K.; Shakir, U. (The Nucleus, 2017)
The Kamlial Formation of middle to late Miocene age is exposed in the hilly area of Karaat, district Karak, Pakistan. It mainly consist of sandstones with intercalations of shales. In order to observe different petrographic features, 16 samples were collected at an average interval of 5 m, from the sandstone unit of the formation. The studied samples mainly consist of quartz, feldspar and rock fragments with an average modal abundance of 45%, 9 % and 15 % respectively and variety of heavy and accessory minerals comprising of muscovite, biotite, garnet, epidote, monazite, tourmaline and zircon. Carbonate is the major cementing material in the studied samples of the Kamlial Formation. By plotting on the triangular diagram majority of the studied samples fall in the field of "feldspathic lithwacke". The high ratio of quartz to feldspar (Q/F=4.8) shows the mineralogical maturity, while, the abundance of matrix suggests that the sandstone is texturally immature even though it comprises of sub-rounded grains and is moderately to well-sorted. Non-undulose to weakly undulose monocrystalline quartz is in a higher proportion in the studied sections whereas the polycrystalline quartz is rare and much less abundant and predominantly consists of two to three sub-grains with straight to only slightly curved sub-grain boundaries. These characteristics of quartz indicates that the source rock is of igneous origin. The friable nature of the sandstone unit makes it a poor building stone but can be used in cement industry and other construction purposes. Kamlial Formation can host potential Uranium deposits because of its environment of deposition.